Polyploidy in urban environments. (June 2022) - Van Drunen, Wendy E.; Johnson, Marc T.J.
Abstract : Polyploidy is a major driver of evolutionary change in plants, but many aspects of polyploidy in natural systems remain enigmatic. We argue that urban landscapes present an unprecedented opportunity to observe polyploidy in action. Integrating polyploid biology and urban evolutionary ecology, we discuss multiple factors expected to promote polyploid formation, establishment, and persistence in urban systems. We develop a predictive framework for the contemporary ecology and evolution of polyploid plants in cities, and through this novel perspective propose that studying polyploidy in an urban context could lead to breakthroughs in understanding fundamental processes in polyploid evolution. We conclude by highlighting the potential consequences of polyploidy in urban environments, and outline a roadmap for research into this currently unexplored field. Highlights: Rapidly expanding urban areas pose a novel suite of challenges to organisms, and these are expected to strongly influence the evolution and ecology of species living in urban environments. Polyploidy (i.e., organisms with >2 chromosome sets) is common among plants and some animals, and polyploidisation is often associated with historical periods of environmental change. Urbanisation and urban environments have the potential to promote polyploidy through the formation and establishment of newly formed polyploids, as well as the preferential persistence of polyploids over diploids within and between species. Polyploidy may play a key role in survival and adaptation to city life, and considering polyploidy in the complex eco-evolutionary dynamics of urban systems may be crucial for predicting the short- and long-term responses of plant species to local and global environmental change.